Use of the utility System Generator for verification of the PLD - based projects - Палагин, А. В.; Опанасенко, В. Н.; Сахарин, В. Г.; Лисовый, А. И. (Problems of Informatization and Control, 2005)
The features of use of the utility System Generator are considered which is a link between systems MATLAB/Simulink and Xilinx Foundation ISE and allows to release the designer from routine work connected to detailed elaboration of the project, to make check of functioning of projected object at the most initial stage of development and by that to reduce terms and to raise quality of development. The approach to designing the FIR-filter with display of signals formed for check of functioning of the project is offered and its PLD-based realization is developed